The Relationship Between Worm Infections and Selenium Intake In Children In The Working Area Of Tabaringan Health Center Makassar City - Shafa Nathania Utami; Nurmadilla, Nesyana; Arlini Wello, Eny; Hadi, Santriani; Darma, Sidrah (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Worm infection is one of the health problems in Indonesia. Worm infections can disrupt nutrient requirements, hinder growth, intellectual development, and affect the immune system, making the body susceptible to other diseases. Selenium is a micronutrient with great potential to influence the immune system. The mechanism of action of selenium includes antioxidant activity, protecting against oxidative damage, maintaining the integrity of the intestinal mucosa, and anti-apoptotic function in the large intestine. Selenium can enhance the host's immune response by increasing the activity of Alternative Activated Macrophages (AAM), which are the main macrophages in fighting intestinal parasitic worms. Research Objective: To determine the relationship between worm infections and selenium intake. Research Method: Analytical research using a cross-sectional approach. Sampling was done using total sampling technique on elementary school children in the Tabaringan Health Center working area in Makassar City, aged 7-9 years. Research Results: The frequency distribution of positive worm infections was 22.2%, equivalent to 8 samples, and negative worm infections were 77.8%, equivalent to 28 samples. Adequacy of selenium intake in the samples showed 16.7% inadequacy, equivalent to 6 samples, and 83.3% adequacy, equivalent to 30 samples. The analysis of the relationship between worm infections and selenium intake yielded a P-value = 0.151. Conclusion: There is no relationship between worm infections and selenium intake in children in the Tabaringan Health Center working area in Makassar City.